Measuring health literacy in Asia: Validation of the HLS-EU-Q47 survey tool in six Asian countries - Duong, T.V.; Aringazina, A.; Baisunova, G.; Nurjanah, -; Pham, T.V.; Pham, K.M.; Truong, T.Q.; Nguyen, K.T.; Oo, W.M.; Mohamad, E.; Tin, Tin Su; Huang, H.L.; et al. (Japan Epidemiological Association, 2017)
Background: Health literacy has been increasingly recognized as one of the most important social determinants for health. However, an appropriate and comprehensive assessment tool is not available in many Asian countries. This study validates a comprehensive health literacy survey tool European health literacy questionnaire (HLS-EU-Q47) for the general public in several Asian countries. Methods: A cross-sectional survey based on multistage random sampling in the target countries. A total of 10,024 participants aged ≥15 years were recruited during 2013e2014 in Indonesia, Kazakhstan, Malaysia, Myanmar, Taiwan, and Vietnam. The questionnaire was translated into local languages to measure general health literacy and its three domains. To evaluate the validity of the tool in these countries, data were analyzed by confirmatory factor analysis, internal consistency analysis, and regression analysis. Results: The questionnaire was shown to have good construct validity, satisfactory goodness-of-fit of the data to the hypothetical model in three health literacy domains, high internal consistency (Cronbach's alpha > 0.90), satisfactory item-scale convergent validity (item-scale correlation ≥0.40), and no floor/ ceiling effects in these countries. General health literacy index score was significantly associated with level of education (P from < 0.001 to 0.011) and perceived social status (P from < 0.001 to 0.016), with evidence of known-group validity. Conclusions: The HLS-EU-Q47 was a satisfactory and comprehensive health literacy survey tool for use in Asia.